Assessment of Surface Quality in Extrusion Honing Process Using Dimensional Analysis Approach - Jayasimha, S. L. N.; Murali Krishna, N. L.; Raju, H. P. (Asian Journal of Engineering and Applied Technology, 2022)
It is critical to obtain the desired surface quality on the internal and external portions of machined part. The estimated level of surface texture can be induced on the exterior regions using traditional finishing processes such as grinding, honing, and so on. While the problem emerges when processing core miniature components such as micro bores, inlet/outlet valves etc. The EH process overcomes this limitation of conventional finishing method. It is a novel micro machining process that extrudes the pressured flow of carrier media blended with abrasives into the confined passage to generate desired level of surface texture. Owing to abrasion process micro machining occurs by taking away the negligible amount of stock material. The present study focuses on the impact of number of passes at the specimen’s entry and exit sides of the carrier media. The improvements in surface finish (Ra) on both side i.e., entry and exit are evaluated as well. A dimensionless expression for Ra is also developed. The relationship is implemented using Buckingham’s π theorem and comparison of developed model is performed with experimental results. SEM analysis is made to portray surface texture produced by selected process parameters such as number of passes, volume fraction and grit size of abrasive grains.